Economies of scale in constructing plant factories with artificial lighting and the economic viability of crop production - Zhuang, Yunfei; Lu, Na; Shimamura, Shigeharu; Maruyama, Atsushi; Kikuchi, Masao; Takagaki, Michiko (Frontiers in Plant Science, 2022)
Since the introduction of LED lamps a decade ago, the plant factory with artificial lighting (PFAL) has been expected to be a savior that overcomes the food crisis, brings food safety, and enhances environmental friendliness. Despite such high expectations, the diffusion of commercial crop production in PFALs has been slow. It has been said that the main reason for this is the huge initial investment required to construct PFALs. This situation has attracted studies to access the economic feasibility of the crop production in PFALs. One thing strange in these studies is that they pay little attention to the scale of their PFALs. PFALs are factories so that they would be subject to economies of scale. If so, the scale of PFALs is an important factor that determines the economic feasibility of plant production in PFALs. However, no study has thus far attempted to examine whether economies of scale exist in the construction of PFALs. To fill this gap, this paper tries to examine, based on the data on the investment cost of PFAL construction collected from various countries and regions in the world, whether economies of scale exist in PFAL construction and, if yes, how it affects the economic viability of the plant production in PFALs by searching for the minimum scale that ensures PFAL crop production economically viable. The results show that economies of scale exist in PFAL construction, and that the production of lettuce, PFALs’ most popular crop, is now well on a commercial basis with the technology level of the most advanced PFAL operators, but strawberries has not reached that stage yet. It is also shown that crop production in PFALs is highly sensitive to changes in the yield and the price of the crops: A 30% decline either in the yield or the price of lettuce would easily bring PFALs bankruptcy. It is discussed that the optimum scale of PFALs would depend not only on the economies of scale but also on the transaction costs, such as the costs of searching and keeping a sufficient number of buyers who offer good and stable crop prices.